Low defect large area semi‐polar (112) GaN grown on patterned (113) silicon. Issue 5 (5th December 2014) - Pristovsek, Markus; Han, Yisong; Zhu, Tongtong; Frentrup, Martin; Kappers, Menno J.; Humphreys, Colin J.; Kozlowski, Grzegorz; Maaskant, Pleun; Corbett, Brian
Abstract We report on the growth of semi‐polar GaN (11<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjkz9drb0" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>2) templates on patterned Si (113) substrates. Trenches were etched in Si (113) using KOH to expose Si {111} sidewalls. Subsequently an AlN layer to prevent meltback etching, an AlGaN layer for stress management, and finally two GaN layers were deposited. Total thicknesses up to 5 <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjkz9g3c7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />μ</alternatives>m were realised without cracks in the layer. Transmission electron microscopy showed that most dislocations propagate along [0001] direction and hence can be covered by overgrowth from the next trench. The defect densities were below <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjkz9dwvp" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />108cm−2</alternatives> and stacking fault densities less than 100 cm <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjkz9dwnk" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />−1</alternatives>. These numbers are similar to reports on patterned r‐plane sapphire. Typical X‐ray full width at half maximum (FHWM) were 500" for the asymmetric (00.6) and 450" for the (11.2) reflection. These FHWMs were 50 % broader than reported for patterned r‐plane sapphire which is attributed to different defect structures and total thicknesses. The surface roughness shows strong variation on templates. For the final surface roughness the roughness of the sidewalls of the GaN ridges at the time of coalescence are critical.